Meta-search and market concentration - Renaud Foucart (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Competing intermediaries search on behalf of consumers among a large number of horizontally differentiated sellers. Consumers either pick the best deal offered by a random intermediary, or compare the intermediaries. A higher number of deal finders has the direct effect of decreasing their search effort, but also increases the incentives for consumers to become informed. A higher share of informed consumers in turns increases the search effort of deal finders, so that the sign of the total effect is ambiguous. If the total effect of lower concentration is to increase search effort, it always decreases the price offered by sellers.
Keywords: 330